Outcomes in non-metastatic treatment naive extremity osteosarcoma patients treated with a novel non-high dosemethotrexate-based, dose-dense combination chemotherapy regimen 'OGS-12'. (November 2017) - Bajpai, Jyoti; Chandrasekharan, Arun; Talreja, Vikas; Simha, Vijai; Chandrakanth, M.V.; Rekhi, Bharat; Khurana, Sachin; Khan, Arif; Vora, Tushar; Ghosh, Jaya; Banavali, Shripad D.; Gupta, Sudeep
Abstract: Purpose: High-dose methotrexate (HDMTX)-based regimens are widely used in osteosarcoma. However, mandatory in-patient treatment with complex pharmacokinetic monitoring requirement precludes its use, especially in resource-constrained settings of low- and middle-income countries (LMICs). Methods: All treatment naive consecutive patients of osteosarcoma were prospectively treated on a novel institutional regimen (named OGS-12) comprising of eight sequential doublets of the following drugs: doxorubicin, cisplatin and ifosfamide in four courses each, given in the neoadjuvant and adjuvant settings. Data were prospectively collected on baseline characteristics, histological response to neoadjuvant chemotherapy (NACT), toxicity, event-free survival (EFS) and overall survival (OS). Results: Between 2011 and 2014, 317 treatment naive patients with extremity osteosarcoma were seen, of whom 237 (75%) were non-metastatic. Majority had high tumour burden, with mean tumour size of 10.45 cm, high serum lactate dehydrogenase (LDH) and serum alkaline phosphatase (SAP) in 71% and 88% respectively. A significant number (34%) were nutritionally challenged. Two-hundred ten of 237 patients were analysable for histological response of which 58% had good response (viable cells ≤10%). At the median follow-up of 34.31 (2–60) months, in intention-to-treat (ITT) analysis, the 5-year EFS and OS were 56% and 75% respectively; the same were 60% and 80% in per-protocol analysis. There was febrile neutropenia (FN) in 56%, grade 3/4 thrombocytopaenia in 22% and anaemia in 47% with two chemotoxic deaths. Ten percent of the patients had grade 3/4 diarrhoea and stomatitis and one patient developed grade 4 acute kidney injury requiring dialysis. Baseline SAP (per-protocol) for EFS and performance status (ITT) for OS were found to be independent variables. Histological response was an independent predictor for EFS and OS in both the analyses. Conclusions: In treatment naive patients with non-metastatic osteosarcoma, OGS-12 protocol, a dose-dense, non-HDMTX-based, novel, economic and easy to administer regimen produces comparable outcomes to international standards, with acceptable toxicity and is worthy of wider clinical application. Highlights: Use ofnovel, dose dense, non-HDMTX-based, low cost, outpatient based, combination chemotherapy protocol "OGS-12". Prospective, single center study of 237 consecutive, treatment-naïve, non-metastatic patients in a rare disease osteosarcoma. Comparable outcomes with international standards, without complex pharmacokinetic monitoring that HDMTX necessitates. Wider clinical applications, especially in resource poor low and middle income countries.